LED-based Fourier transform spectroscopy of 16O12C18O and 12C18O2 in the 11, 260–11, 430 cm−1 range. (July 2016) - Serdyukov, V.I.; Sinitsa, L.N.; Lugovskoi, A.A.; Borkov, Yu.G.; Tashkun, S.A.; Perevalov, V.I.
Abstract: The absorption spectrum of the 16 O 12 C 18 O and 12 C 18 O2 carbon dioxide isotopologues has been recorded in the 11, 260– 11, 430 cm −1 spectral range using Bruker IFS 125 HR Fourier transform spectrometer with resolution 0.05 cm −1 at temperature 297 K and path length 24 m. The 18 O enriched sample of carbon dioxide at total pressure 96.5 mbar was used for these purposes. The spectrometer used LED emitter as a light source. This gave possibility to reach the minimal detectable absorption coefficient α min 1.4×10 −7 cm −1 using 23, 328 scans. In the recorded spectrum we have assigned the 00051–00001 band for both 16 O 12 C 18 O and 12 C 18 O2 isotopologues using the predictions performed within the framework of the method of effective operators. The line positions and intensities of the observed bands are found. The comparison of the observed and predicted line positions and intensities is performed confirming good accuracy of the predictions. The spectroscopic parameters for the observed bands are determined. Highlights: LED-based Fourier transform spectroscopy. Line positions and intensities of 5 ν3 band of 16 O 12 C 18 O and 12 C 18 O2 are measured. Results are compared to the predictions.